English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories
4

substitution method.
6x-y=-4
2x+2y=15

2006-11-04 08:44:38 · 8 answers · asked by Anonymous in Science & Mathematics Mathematics

please show work, i know however, that the answer is (1/2,7)

2006-11-04 12:04:43 · update #1

8 answers

6x-y=-4.......Equation 1
2x+2y=15.......Equation 2
Two equations, two unknowns.
Consider Eq. 2
2x+2y=15
2(x + y) = 15
x + y = 15/2
x = 15/2 - y
Now substitute the derived value of 'x' in Eq. 1
6x-y=-4
6(15/2 - y) - y = -4
6[(15-2y)/2] - y =-4
3(15 - 2y) - y = -4
45 -6y - y = -4
-7y = -4-45
-7y = -49
7y = 49
y = 49/7 = 7
Now substitute the value of 'y' in Eq. 1
6x-y=-4
6x - 7 = -4
6x = 7-4
6x = 3
x = 3/6
x = 1/2
(x = 1/2, y = 7)

2006-11-05 03:03:03 · answer #1 · answered by Akilesh - Internet Undertaker 7 · 0 0

6 x - y= -4 to begin with you have to solve for x or y, in this case y is easier
-6 x -6 x
________________
- y= -4 - 6x but y cannot remain negative therefore
-1(-y= -4 - 6x) = y= 4 + 6 x

you have now solved for y substitue it in the second equation

2x+ 2(4+6x) = 2x + 8 +6x now you must isolate the x's so move the 8 over to the
- 8 other side of the equal sign
__________________________
-8 = 2x + 6x combine like terms
__________________________
-8 = 8x
______
8 now further siloate the x but dividing the 8x by 8 (remember the 8/ -8 will come out a negative number)

x= -1 now that the x is solved for plug it back into one of the orginal equations to completely solve for y

2(-1) + 2y= 15
-2 + 2y = 15 now get rid of the 2
+ 2 +2
____________

2y= 17 now divide the 2 out of the x (do both sides)
__________
2 2

y= 17 over 2 (17/2) or 8. 5 or 8 1/2

2006-11-04 17:03:08 · answer #2 · answered by trish the dish 3 · 0 1

There are far too many ways u can do this.
6x-y=4, y=6x-4
sub this into the eqn 2x+2y = 15.

Hope this helps=)

2006-11-04 16:48:14 · answer #3 · answered by luv_phy 3 · 0 0

from the first equation:
y = 6x+4
substitute for y in the second equation:
2x + 2(6x+4) = 15
so 2x +12x + 8 = 15
so 14x = 7
so x = 2
and from y = 6x + 4 we have y = 16

2006-11-04 16:47:50 · answer #4 · answered by ? 7 · 0 1

2(6x-y)=(-4)(2) 3-Y=-4
2x+2y=15 -y=-7
y=7
12x-2y=-8
+2X+2Y=15 (1/2,7)
------------------
14X=7
X=1/2

3-Y=-4
-y=-7
y=7

(1/2,7)

y=7

2006-11-04 18:25:57 · answer #5 · answered by :) 3 · 2 0

6x-y=-4
y=6x+4

2x+2y=15
2x+2(6x+4)=15
2x+12x+8=15
14x=7
x=.5
y=6x+4=6*.5+4=3+4=7

check
6*.5-7=3-7=-4
2*.5+2*7=1+14=15

2006-11-04 17:06:40 · answer #6 · answered by yupchagee 7 · 1 0

How can all of you be idiots?

Starting with the first guy's answer...I mean he had good intentions but ****** up the math.

x= 0.5
y=7

plug that into the equation and double check your math if you want.

Close this question down and please stop confusing this young cheater.

2006-11-04 17:20:31 · answer #7 · answered by Carlos B 1 · 1 1

(2,20)

2006-11-04 16:48:56 · answer #8 · answered by      7 · 0 1

fedest.com, questions and answers